2016
DOI: 10.4103/1319-2442.178553
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome in hemodialysis patients

Abstract: Restless legs syndrome (RLS) is a neurological disorder characterized by uncomfortable sensation of paresthesia in legs that subsequently causes involuntary and continuous movement of the lower limbs, especially at rest. Its prevalence in hemodialysis is more than that in the general population. Different risk factors have been suggested for RLS. We studied the prevalence and risk factors of RLS in 137 hemodialysis patients followed up at our center. The patients completed at least three months on dialysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
1
4
1
4
Order By: Relevance
“…In contrast to some studies [4, 810], we found no significant association between diabetes mellitus type 2 and RLS among ESRD patients. It is not clear whether diabetes mellitus itself or diabetic peripheral neuropathy is the dominant risk factor [33].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to some studies [4, 810], we found no significant association between diabetes mellitus type 2 and RLS among ESRD patients. It is not clear whether diabetes mellitus itself or diabetic peripheral neuropathy is the dominant risk factor [33].…”
Section: Discussioncontrasting
confidence: 99%
“…Our result reveals that RLS is more common in female ESRD patients (OR = 2.729, p = 0.032), similar to some other studies [5, 8, 24]. In general population studies, RLS is consistently more common in females [23, 25], although one German study found this was explained by previous pregnancies, such that null-parous women had similar RLS rates as men [25, 26].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Chronic kidney disease, diabetes, and oxidative stress are associated with uremic RLS [ 18 ]. Some studies say polyneuropathy is the highest risk factor of RLS in diabetic patients as it affects catecholaminergic systems by reducing the dopaminergic content, thus affecting the midbrain and striatum, which is crucial for RLS [ 7 ].…”
Section: Reviewmentioning
confidence: 99%